2019
DOI: 10.1002/ceat.201800478
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Magnesium Orotate‐Loaded Chitosan Polymer Nanoparticles for a Drug Delivery System

Abstract: The drug release properties of magnesium orotate (MgOr) encapsulated in the chitosan (CS) cavity and the complexation behavior between MgOr and CS were investigated. The MgOr-loaded CS nanoparticles (MgOrCSNPs) were characterized by differential scanning calorimetry, Fourier transform infrared spectroscopy, X-ray diffraction, transmission electron microscopy, and scanning electron microscopy with energy-dispersive X-ray spectroscopy. MgOr was successfully encapsulated into the CS cavity. Results with 3-(4,5-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Analysing the DTA curve of MO-C it can be observed the appearance of a new endothermic peak at 332°C attributed to the decomposition of C, which is in concordance with previous results in literature [8].…”
Section: Ft-ir Spectroscopysupporting
confidence: 92%
See 1 more Smart Citation
“…Analysing the DTA curve of MO-C it can be observed the appearance of a new endothermic peak at 332°C attributed to the decomposition of C, which is in concordance with previous results in literature [8].…”
Section: Ft-ir Spectroscopysupporting
confidence: 92%
“…Being organic compounds, the theoretical mass loss of excipients should be 100%, however in our case the mass loss in the case of organic excipients (32.37% CS, 43.1% C, 19.9 CC) is much smaller since the experiments were performed in nitrogen. Literature survey revealed that the decomposition of CS (same as C) take place in one stage, in the temperature range 300 -400°C [8,22], which confirm our results. L and S, in combination with MO, showed significant thermal changes as displayed in Figure 5a and Figure 5b.…”
Section: Thermal Analysissupporting
confidence: 90%
“…However, among the many obstacles facing these therapeutic agents is their limited absorption and retention by cancer cells which also lead to toxic effects in normal tissue cells [1][2][3][4]. In this quest, the development of nanoparticle formulations of different therapeutic agents served in providing a better delivery tool of chemotherapies with better dosage and targeting precision to the tumor site [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%